Effect of tcdR Mutation on Sporulation in the Epidemic Clostridium difficile Strain R20291 - Girinathan, B. P.; Monot, M.; Boyle, Daniel L.; McAllister, K. N.; Sorg, J. A.; Dupuy, B.; Govind, Revathi (My University, 2017)
Clostridium difficile is an important nosocomial pathogen and the leading cause of hospital-acquired diarrhea. Antibiotic use is the primary risk factor for the development of C. difficile-associated disease because it disrupts normally protective gut flora and enables C. difficile to colonize the colon. C. difficile damages host tissue by secreting toxins and disseminates by forming spores. The toxin-encoding genes, tcdA and tcdB, are part of a pathogenicity locus, which also includes the tcdR gene that codes for TcdR, an alternate sigma factor that initiates transcription of tcdA and tcdB genes. We created a tcdR mutant in epidemic-type C. difficile strain R20291 in an attempt to identify the global role of tcdR. A site-directed mutation in tcdR affected both toxin production and sporulation in C. difficile R20291. Spores of the tcdR mutant were more heat sensitive than the wild type (WT). Nearly 3-fold more taurocholate was needed to germinate spores from the tcdR mutant than to germinate the spores prepared from the WT strain. Transmission electron microscopic analysis of the spores also revealed a weakly assembled exosporium on the tcdR mutant spores. Accordingly, comparative transcriptome analysis showed many differentially expressed sporulation genes in the tcdR mutant compared to the WT strain. These data suggest that regulatory networks of toxin production and sporulation in C. difficile strain R20291 are linked with each other. IMPORTANCE C. difficile infects thousands of hospitalized patients every year, causing significant morbidity and mortality. C. difficile spores play a pivotal role in the transmission of the pathogen in the hospital environment. During infection, the spores germinate, and the vegetative bacterial cells produce toxins that damage host tissue. Thus, sporulation and toxin production are two important traits of C. difficile. In this study, we showed that a mutation in tcdR, the toxin gene regulator, affects both toxin production and sporulation in epidemic-type C. difficile strain R20291.
Citation: Girinathan, B. P., Monot, M., Boyle, D., McAllister, K. N., Sorg, J. A., Dupuy, B., & Govind, R. (2017). Effect of tcdR Mutation on Sporulation in the Epidemic Clostridium difficile Strain R20291. Msphere, 2(1), 14. doi:10.1128/mSphere.00383-16
Keywords: Clostridium Difficile; Sporulation; Toxin Gene Regulation; Toxin Gene-Expression; Bacillus-Subtilis; Sigma-Factor